The effect of withholding salt on the growth and condition of steers. - Smith, E.F.; Parrish, D.B.; Clawson, A.J. (Kansas Agricultural Experiment Station, 2012)
Then good quality Hereford steer calves were used in this study. They were divided into two equal lots. Both lots were treated similarly except salt was withheld from one lot. The calves were started on the test December 14, 1949, wintered, used in a spring digestion trial, full-fed in dry lot and marketed on November 2, 1950.
Keywords: Beef; Salt; Wintering phase; Digestibility